Managers in the context of small business growth: a qualitative study of working conditions and wellbeing - Elena Ahmadi; Daniel Lundqvist; Gunnar Bergström; Gloria Macassa (BMC Public Health)
Abstract Purpose In view of the importance of managers’ wellbeing for their leadership behaviour, employee health, and business effectiveness and survival, a better understanding of managers’ wellbeing and working conditions is important for creating healthy and sustainable businesses. Previous research has mostly provided a static picture of managers’ wellbeing and work in the context of small businesses, missing the variability and dynamism that is characteristic of this context. Therefore, the purpose of this study is to explore how managers in small companies perceive their working conditions and wellbeing in the context of business growth. Methods The study is based on qualitative semi-structured interviews with 20 managers from twelve small companies. Content and thematic analysis were applied. Results The findings indicate that a manager’s working environment evolves from its initial stages and through the company’s growth, leading to variations over time in the manager’s experiences of wellbeing and work–life balance as well as changes in job demands and resources. Managers’ working situation becomes less demanding and more manageable when workloads and working hours are reduced and a better work–life balance is achieved. The perceived improvement is related to changes in organizational factors (e.g. company resources), but also to individual factors (e.g. managers’ increased awareness of the importance of a sustainable work situation). However, there were differences in how the working conditions and wellbeing changed over time and how organizational and individual resources affected the studied managers’ wellbeing. Conclusions This study shows that, in the context of small business, managers’ working conditions and wellbeing are dynamic and are linked to growth-related changes that occur from the start of organizational activities and during periods of growth. In addition, the findings suggest that changes in managers’ working conditions and wellbeing follow different trajectories over time because of the interaction between organizational and personal factors.